p53 in nonneoplastic central nervous system lesions: An immunohistochemical and genetic sequencing study - (:unkn) unknown (My University, 2002)
OBJECTIVE: Immunostaining for p53 commonly is considered a marker of neoplasia. Previous studies of nonneoplastic processes have yielded conflicting results. METHODS: To test the assumption that p53 immunoreactivity indicates neoplasia, we examined 60 formalin-fixed, paraffin-embedded biopsies of nonneoplastic central nervous system lesions, including gliosis (n = 12), infarction (n = 9), demyelinating disease (n = 23), progressive multifocal leukoencephalopathy (n = 11), and herpes simplex virus encephalitis (n = 5). Diffuse astrocytomas (n = 50) of World Health Organization Grades 2 to 4 also were studied, as were six control autopsy brains. The avidin-biotin-peroxidase complex method was used with commercially available monoclonal antisera to both p53 (clone DO7; Dako, Carpinteria, CA) and mdm2 (Dako), a protein known to stabilize p53. Two samples of each nonneoplastic lesion also were subjected to deoxyribonucleic acid isolation, amplification, and sequencing of exons 5 to 8 of TP53. RESULTS: Although it was low level in most instances, p53 immunoreactivity was noted in all but normal control samples. In reactive lesions, staining was largely observed in astrocytes and histiocytes. Scant oligodendroglia also were labeled in demyelinating disease. The progressive multifocal leukoencephalopathy samples revealed exceptionally strong staining in astrocytes and infected oligodendrocytes. Staining also was noted in occasional endothelial cells and neurons, and in rare lymphocytes. Immunoreactivity for mdm2, studied only in nonneoplastic lesions, was moderate to strong in all cases and limited to reactive astrocytes and histiocytes. No TP53 mutations were noted in the nonneoplastic lesions studied. To some extent, all astrocytomas exhibited p53 immunopositivity, particularly high-grade lesions. CONCLUSION: p53 immunoreactivity is not limited to astrocytomas, but it can be observed in lesions that often are mistaken for glioma. No TP53 mutations accompany p53 expression in nonneoplastic lesions, and mdm2 may be responsible for persistence of p53 expression in these processes.
Keywords: Astrocytoma; Demyelinating disease; Gliosis; Infarction; Mdm2; Mutation analysis; p53; Viral encephalitis